The Phenomenon of Unregistered Marriages: Problems and Solution - Desmal Fajri; Felti Novira (Universitas Muhammadiyah Purwokerto, 2023)
In 2022 there are 20 marriages in Batu Gajah Village, 11 or 55 percent of marriages are not registered and 45 percent of marriages are registered. According to the applicable laws and regulations, a marriage is valid if it is registered. Marriages for people who are Muslim are registered at the Office of Religious Affairs and for non-Muslims at the Civil Registry Office. This study aims to analyze the factors that cause marriages not to be recorded in Nagari Batu Gajah. This study uses an empirical juridical approach, which is a research approach to secondary data first and then continues to conduct primary data research in the field. Primary data was obtained through interviews with a Ninik Mamak as a community figure and 10 undocumented marriages. Then the empirical data were analyzed descriptively and qualitatively. Based on the results of the study, the factors causing marriages not to be registered in Nagari Batu Gajah were age, cost, pregnancy out of wedlock, access to the KUA office that was far away, polygamy, understanding of the rules, elopement, pregnancy out of wedlock and did not get permission from the Ninik Mamak. Then the way to deal with unregistered marriages is to socialize to the community by the Office of Religious Affairs regarding the marriage law and improve road access to the Office of Religious Affairs and the community must comply with local customary norms.Keywords: Marriage, Unregistered Marriage, Religious Affairs Office